Gutter child : a novel - Richardson, Jael Ealey, 1980- (Harper Avenue, an imprint of HarperCollins Publishers Ltd., 2021)
"A fierce and illuminating debut from FOLD founder Jael Richardson about a young woman who must find the courage to determine her own future and secure her freedom. Set in an imagined world in which the most vulnerable are forced to buy their freedom by working off their debt to society, Gutter Child uncovers a nation divided into the privileged Mainland and the policed Gutter. In this world, Elimina Dubois is one of only 100 babies taken from the Gutter and raised in the land of opportunity as part of a social experiment led by the Mainland government. But when her Mainland mother dies, Elimina finds herself all alone, a teenager forced into an unfamiliar life of servitude, unsure of who she is and where she belongs. Elimina is sent to an academy with new rules and expectations where she befriends Gutter children who are making their own way through the Gutter System in whatever ways they know how. When Elimina's life takes another unexpected turn, she will discover that what she needs more than anything may not be the freedom she longs for after all. Richardson's Gutter Child reveals one young woman's journey through a fractured world of heartbreaking disadvantages and shocking injustices. Elimina is a modern heroine in an altered but all too recognizable reality who must find the strength within herself to forge her future and defy a system that tries to shape her destiny."--